2013
DOI: 10.1136/annrheumdis-2012-202444
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and hypoxia-inducible factor-1α provoke toll-like receptor signalling-induced inflammation in rheumatoid arthritis

Abstract: Our findings suggest that hypoxia and HIF-1α may function in conjunction with TLR-stimulated innate immune responses to drive inflammation in RA. This pathway may serve as a therapeutic target for the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 22 publications
3
78
0
Order By: Relevance
“…Furthermore, positive the scores for synovitis (a), the score for pannus formation (b), the score for bone destruction (c), and the levels of VEGF (d) and HIF-1α (e) in the synovium feedback regulation of the HIF-1α and VEGF pathways can trigger angiogenesis during hypoxia [45]. In vitro studies have confirmed that the absence of HIF-1α attenuates angiogenesis through a VEGF-dependent mechanism [46].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, positive the scores for synovitis (a), the score for pannus formation (b), the score for bone destruction (c), and the levels of VEGF (d) and HIF-1α (e) in the synovium feedback regulation of the HIF-1α and VEGF pathways can trigger angiogenesis during hypoxia [45]. In vitro studies have confirmed that the absence of HIF-1α attenuates angiogenesis through a VEGF-dependent mechanism [46].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the association of smoking with disease occurrence in individuals who carry the shared epitope and worse disease outcome is well established [18]. It is confirmed that local factors such as hypoxia, which is thought to be important in Immune signal transduction, are also relevant [19]. However, the detailed molecular mechanisms of the disease are still elusive.…”
Section: Discussionmentioning
confidence: 95%
“…Under hypoxic conditions, disruption of HIF-1α in Müller cells attenuates the increases of retinal vascular leakage and inflammation 13. Fanlei Hu et al demonstrated that hypoxia and HIF-1α potentiate TLR signalling-induced inflammation in rheumatoid arthritis 14. TLR signalling-induced innate immunity is linked to the hypoxic response through NF-κB in macrophages 15.…”
Section: Discussionmentioning
confidence: 99%